2021
DOI: 10.1186/s12903-021-01547-7
|View full text |Cite
|
Sign up to set email alerts
|

Online dental teaching practices during the COVID-19 pandemic: a cross-sectional online survey from China

Abstract: Background Coronavirus disease 2019 (COVID-19) emerged in China in December 2019. The COVID-19 pandemic hindered dental education, as school buildings were closed. Online dental teaching provided an alternative teaching tool for dental education. However, the efficiency of online dental teaching and student preferences for online dental teaching are unclear. Aim To investigate the satisfaction with online dental teaching practices among undergradua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
4
20
0
1
Order By: Relevance
“…We found that most of the dental students were not satisfied with online learning and preferred campus-based courses to online education, which is corroborated by previous research [1,42,43]. Since dental education is composed of several components, such as lectures/tutorials, problem-based learning interactions, research-based learning, simulated training courses, and clinical skills training [42,43], studies reported that online classes are not feasible for professional dental courses [42,44]. Other studies suggested that blended learning may be useful for dental education, with lectures/tutorials carried out remotely and clinical/professional training courses arranged on-site [41,44].…”
Section: Discussionsupporting
confidence: 89%
“…We found that most of the dental students were not satisfied with online learning and preferred campus-based courses to online education, which is corroborated by previous research [1,42,43]. Since dental education is composed of several components, such as lectures/tutorials, problem-based learning interactions, research-based learning, simulated training courses, and clinical skills training [42,43], studies reported that online classes are not feasible for professional dental courses [42,44]. Other studies suggested that blended learning may be useful for dental education, with lectures/tutorials carried out remotely and clinical/professional training courses arranged on-site [41,44].…”
Section: Discussionsupporting
confidence: 89%
“…15 A new ideology was given by Kumar et al wherein he states that E learning can be used as a platform for providing elective classes to cover the challenging topics as well as techniques for the exam going undergraduates. 16 Dentistry requires hands on training for developing the clinical skills. An initiative by the University of Nebraska provides a database with digitalised slides for virtual microscopy.…”
Section: Discusssionmentioning
confidence: 99%
“…9 Faculty development programs can also be conducted to improve the skills to deliver both theoretical and practical knowledge. 16 Further, a visual explanation of practical works should be augmented as it is considered as the strength of e-learning. 20…”
Section: Discusssionmentioning
confidence: 99%
“…In addition, students are encouraged to learn by themselves, use online learning resources, and discover the latest academic developments and in-anxiety, and suicidal tendencies associated with the Covid 19 outbreak, and an increase in depression symptoms in those with longer school years. [19][20][21]…”
Section: Challenges In Dental Educationmentioning
confidence: 99%